Resilience and Hybridization of Development of Small and Medium Towns in Poland - Drobniak, Adam (Olsztyn Economic Journal, 2019)
This paper aims to initially evaluate the socio and economic resilience of small and medium sized town in Poland made in the context of hybridization of development. The article refers to the issues of development of small and medium sized towns as well as to the urban resilience concept recognized in the attributes approach. Empirically, an initial assessment of resilience was carried out for all towns up to 100,000 residents in Poland using quantitative methods based on indicators of dynamics. Then, using cluster analysis along with the Euclidean distance the paper presents its findings in spatial dimension. The results indicate a very high level of differentiation in socio and economic urban resilience of the surveyed towns. The dynamics of their development is highly unbalanced, while the overall picture of resilience of the examined towns indicates a hybrid pattern of their development.